Contribution of the socio-economic management control to steering balanced and sustainable company overall performance. Issue 2 (10th July 2017) - Voyant, Olivier; Bonnet, Marc; Tabchoury, Patrick; Datry, Frantz
Abstract : Purpose: The purpose of this paper is to show that steering overall performance requires not only juxtaposing indicators focused on economic, social and environmental performance but also negotiating the measurement of performance metrics with all the stakeholders. Design/methodology/approach: This is an action-research and intervention-research project aimed at experimenting an integrated and negotiated management control system for overall performance. The choice for the case study is a hospital in the Middle East that practices green management and that has to be self-financed while accepting all patients, even those who cannot pay. Findings: The integration of the three dimensions of overall performance requires involving all stakeholders in the implementation of innovative management control. Research limitations/implications: The case is a pilot experiment and shows the conditions for an appropriate design of an overall performance management control methodology. However, further experiments should be carried out to shed light on the factors that form invariants regarding integrated performance log-books. Practical implications: The study design is that of a management control methodology that enables the short- and long-run economic impacts of social and environmental performance. Social implications: The action-research process has proved to be a learning experience for the hospital and both internal and external stakeholders. However, replicability remains to be proven through experimenting the method in various settings. Originality/value: This paper shows the need for negotiation of overall performance with all stakeholders to design and implement an appropriate participative approach to management control.